Proses Penyiaran Syariah - Gani Hakim Abdillah; Rivan Rio Saputra; Mochamad Sean Fahreza; Muhammad Fadhil Wicaksono (Indo Publishing, 2025)
Sharia broadcasting is an Islamic da'wah medium delivered through television and radio programs. This study aims to examine the production process, content, and impact of sharia broadcasting programs, using case studies of Islam Itu Indah (Trans TV), Hikmah Fajar (TVRI), and Kajian Subuh (Radio Dakta FM). A descriptive qualitative method was used. The results show that the broadcasting process involves planning Islamic content, communicative production, and post-production that upholds da'wah ethics. The programs are educational and religious in nature, presented in the form of lectures, audience interaction, and Qur’anic recitation. Sharia broadcasting effectively enhances public Islamic literacy but faces challenges such as commercialization and celebrity preachers. Content supervision and quality improvement of Islamic broadcasters are needed to maintain the authenticity and depth of the da'wah message.